Study of experience of organization of labour studies is in folk schools of Katerinoslavshchina in modern practice of higher school (Pedagogy of Higher and Secondary Education, 2014)
Yemeleva A. П. Study of experience of organization of labour studies is in folk schools of Katerinoslavshchina in modern practice of higher school.The article discusses the historical and pedagogical experience of labor education in public schools of Katerynoslavska province (late XIX – early XX century). The educational-methodical complex named «The Development of labor studies in folk high schools of Katerynoslavshchina (the end of XIX – the beginning of XX century)» was made according to the results of the research to deepen the knowledge of theory and history of pedagogy, ethnology, history of culture.
Keywords: employment training; public school teaching complex; teaching complex